aBuried and Forgotten but Not Deada: Reflections on aUbuntua In Environmental Conservation in Southeastern Zimbabwe (Global Journal of Human-Social Science, 2012)
The subject of ubuntu has taken a central stage in academic research on Africa in recent years. In Zimbabwe as in Africa in general, academics and researchers have tussled with various aspects of this subject, with most research emphasizing the contribution of ubuntu in business, education, healthy, philosophy and legal systems. Ramose (1999), Teffo (1995) and Shutte 2001, for example, explore the importance of ubuntu in African philosophy, especially in areas such as morality/ethics, epistemology, logic and metaphysics. Mbigi and Maree (1995), Goduka and Swadener (1999) and Prinsolo (1995) focus on the value of ubuntu in business, education and healthy fraternity respectively. Still other studies (Cornell ny; Sindane 1995) have exported the concept of ubuntu into legal systems and politics. Surprisingly, insignificant attention has been devoted to exploring the value of ubuntu in environmental conservation. This paper examines the extent to which since time immemorial, ubuntu helped to conserve the ‘natural’ environment and to save it from deterioration by human action. The piece marshals the concept of ubuntu and positions it against the southeastern Zimbabwe, in particular, Norumedzo and Mukanganwi landscapes. It argues for the revival and reinstitution of ubuntu to complement efforts by Science in biodiversity conservation. The argument finds its justification in ubuntu’s profound respect for life (of both human and non-human beings) which makes it a potential drive for sustainable development and biodiversity conservation.
Keywords: Ubuntu; natural environment; conservation; southeastern Zimbabwe; Africa